PENDAPATAN USAHATANI KACANG TANAH DI DESA TAGAWITI KECAMATAN ILE APE KABUPATEN LEMBATA - Asnah Asnah; Virgilius Natal (BUANA SAINS, 2009)
Peanut has been known and developed by farmers in Indonesia. Besides of easy and simple in technique to grow, peanut can cultivate in all type of soils, resistant of weather changes, and disease and insect attack, and has widely marketing prospect. This research is aimed to study cost, revenue, income, profit and efficiency of peanut farming. Location is purposively determine in Tagawiti village, Ile Ape district, Lembata area, by using random sampling, gradually based on land wide. Analysis data method is research result is tabulated and interpreted as equal as analysis result and goal